ISLAM DAN PLURALISME AGAMA - Miftahul Ula (UIN K.H. Abdurrahman Wahid Pekalongan, 2009)
Islam is the last religion revealed by Allah to the whole human beings in the world as peace for all, and perfect religion before Islam. Islam with its universal and inclusive teaching is the only religion that can receive other religion as a faith understanding. Formally, Qur’an also acknowledges the prophets of religions before Islam and does not discriminate other religions. Islam does not make the difference of religion not be kind, not make good social relationship, and not do justice in social life as long as it does not bring about faith contamination and does not get across Muslim community